2016
DOI: 10.1051/0004-6361/201527175
|View full text |Cite
|
Sign up to set email alerts
|

Fossil group origins

Abstract: Context. Fossil groups (FG) are expected to be the final product of galaxy merging within galaxy groups. In simulations, they are predicted to assemble their mass at high redshift. This early formation allows for the innermost M * galaxies to merge into a massive central galaxy. Then, they are expected to maintain their fossil status because of the few interactions with the large-scale structure. In this context, the magnitude gap between the two brightest galaxies of the system is considered a good indicator … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 74 publications
1
23
0
1
Order By: Relevance
“…This lack of substructure in fossil halos has been interpreted as a challenge for the hierarchical formation (D'Onghia & Lake 2004); nevertheless, this is still a puzzle and a matter of debate (Zibetti et al 2009). The galaxy population in FSs also shows evidence of substructure similar to nonFSs, arguing against the relaxed and old dynamical age of FSs (Zarattini et al 2016). …”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…This lack of substructure in fossil halos has been interpreted as a challenge for the hierarchical formation (D'Onghia & Lake 2004); nevertheless, this is still a puzzle and a matter of debate (Zibetti et al 2009). The galaxy population in FSs also shows evidence of substructure similar to nonFSs, arguing against the relaxed and old dynamical age of FSs (Zarattini et al 2016). …”
Section: Introductionmentioning
confidence: 93%
“…The catalog turned out to have 89 galaxies brighter than m r ∼ 18.0 with measured radial velocities. Using this data-set from SDSS-DR6, Zarattini et al (2016) reported that the mean velocity of group (V c ) was 15498 km s −1 , and the velocity dispersion σ c = 259 km s −1 . The estimate of L X allowed us to calculate r 200 = 0.96 Mpc (Zarattini et al 2014) using the relations from Böhringer et al (2007) and Arnaud et al (2005).…”
Section: The Data For Rxj0752436+455653mentioning
confidence: 99%
See 1 more Smart Citation
“…Aguerri et al (2011) analyzed one FG finding no significant galaxy substructure. Nevertheless, the study from Zarattini et al (2016) on a larger sample of fossils, found that FGs show similar amounts of galaxy substructure as non-FGs. In addition, no differences have been found on the large-scale structure around fossil systems.…”
Section: Introductionmentioning
confidence: 95%
“…Extreme examples of the correlation between group age and the central-to-satellite mass ratio are fossil groups and clusters (e.g. Jones et al 2003;Zarattini et al 2016), in which the most massive satellite of the system is at least two magnitudes fainter than the central, brightest galaxy. D' Onghia et al (2005) and Dariush et al (2010), among others, showed that in a hierarchical universe, these fossil groups are expected to have been formed at much higher redshift than other groups of the same mass.…”
Section: Discussionmentioning
confidence: 99%